Prevalence of psychiatric co-morbidity among patients attending dental OPD and the role of consultation-liaison psychiatry in dental practice in a tertiary care general hospital - Ray, Pradip K (Indian J Dent, 2015)
BACKGROUND: Psychiatric co-morbidities are frequent among patients attending dental OPD, some of which go unrecognized and hence untreated. AIMS: The present study has been carried out to detect the psychiatric co-morbidities among dental patients and determine the scope of consultation-liaison (C-L) psychiatry in a rural teaching hospital regarding comprehensive management of the patients. SETTINGS AND DESIGN: This cross-sectional, descriptive type study was conducted in a multi-speciality tertiary care teaching hospital in the northern part of West Bengal, India. MATERIALS AND METHODS: One hundred patients attending the dental OPD were randomly included in the study and every patient was consecutively referred to psychiatry department for assessment, during the period from 1(st) November 2013 to 30(th) April 2014. All referred patients were clinically examined and psychiatric co-morbidity was assessed by the help of General Health Questionnaire (GHQ)-28 and Mental Status Examination. STATISTICAL ANALYSIS USED: The data were subjected to statistical package for social sciences (SPSS), version 16, and statistically analyzed using Cross tab and Chi test. P <0.05 was considered to be statistically significant. RESULTS: The commonest dental illness was dental caries (22%). More than two-third of the patients had psychiatric co-morbidity according to GHQ-28 total score. Sixty-eight patients were diagnosed to have mental disorder on mental status examination. Somatoform disorder (25%) was the commonest type of mental disorder, followed by mixed anxiety and depression (14%). CONCLUSIONS: This study has pointed the need for psychological examination of patients visiting dental specialty with unexplained physical symptoms. Such patients can be identified and treated, provided a psychiatric consultation service exists.